CHEMICAL ANALYSIS OF LITSEA CUBEBA ESSENTIAL OIL HARVESTED FROM ARUNACHAL PRADESH, INDIA AND ESTIMATION OF MOSQUITO REPELLENT ACTIVITY WITH REFERENCE TO NETWORK ANALYSIS: CHEMICAL ANALYSIS MOSQUITO REPELLENT ACTIVITY LITSEA CUBEBA ESSENTIAL OIL ARUNACHAL PRADESH - NAYANMONI BORUAH; SUDARSHANA BORAH; PRIYANKA SARKAR; HEMANTA KUMAR SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Litsea cubeba is a medicinal plant indigenous to Southeastern Asia. The fruit of the plant is rich in essential oil. A study has been carried out to investigate on the chemical composition of essential oil of the plant harvested from Arunachal Pradesh and to find out its mosquito repellent activity. Methods: The essential oil has been isolated from the fresh fruits by hydrodistillation and analyzed by gas chromatography–mass spectrometry. Compound-compound network analysis was carried out in SPSS software (IBM SPSS Statistics 20) followed by the construction of the network using Cytoscape 3.5.0. Mosquito repellent study was carried out using standard procedure. Results: Citronellal (17.32%), citronellol (13.85%), nimbiol (9.35%), and myrcenol (7.40%) were the major constituents of the essential oil and the essential oil illustrated 3 h mosquito repellent activity against Aedes aegypti mosquitoes. Conclusion: From this investigation, a significant difference could be observed in the essential oil composition from the previously reported data of other regional areas of Asia, and furthermore, the essential oil possesses significant mosquito repellent activity.